URGENSI PENENTUAN KIBLAT DENGAN TEKNOLOGI - Rahmi, Nailur (JURIS (Jurnal Ilmiah Syariah), 2011)
In general, different perspectives upon the position of kiblat still take place among Moslems due to the way to determine the position which is believed too simple. Consequently, when the position is determined by more sophisticated and accurate tools, differences take place. Such differences deal with the determination of the course of Mekkah due to differences in measuring the degree which in turn will affect expected position. As a result, the position of kiblat  is not suitable with the Islamic law anymore. Conversely, determining the position of kiblat by using more valid and accurate technology will ensure the accurate position of kiblat itself and guarantee full belief in performing prayer (shalat).